Comparison of the Safety and Efficacy between Transperitoneal and Retroperitoneal Approach of Laparoscopic Ureterolithotomy for the Treatment of Large (>10mm) and Proximal Ureteral Stones: A Systematic Review and Meta-analysis - Chen, Hualin; Chen, Gang; Chen, Han; Pan, Yang; Zhu, Yunxiao; Gao, Fei; Jin, Xiaoxiang (Urology Journal, 2020)
Purpose: We aimed to compare the safety and efficacy between laparoscopic transperitoneal ureterolithotomy (LTU) and laparoscopic retroperitoneal ureterolithotomy (LRU) in the treatment of large (>10mm) and proximal ureteral stones. Materials and Methods: Electronic databases, including PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus were searched through December 2019. Comparative studies comparing the two approaches were included. The primary outcome was a single-procedure success rate; the secondary outcomes included operative time, hospital duration, and complications (according to the Clavien-Dindo Grade). Newcastle–Ottawa scale (NOS) and the modified Jadad scale were used to evaluate the quality of the included studies. The Egger's test estimated publication bias. The meta-analysis was performed by Review Manager 5.3 and STATA 15.0. Results: Seven studies, involving 125 participants in LTU group and 128 in LRU group, were included in the study. The results suggested that both single-procedure success rate and the rate of postoperative paralytic ileus were significantly higher in the LTU group than in the LRU group (95.2% vs 87.5%, 95% CI: .00-.16, RD = .08, P = .04; 10.4% vs 0, 95% CI: .02- .19, RD = .10, P = .02, respectively). No publication bias of the primary outcome was observed with the Egger’s test (P = .117). No significant differences were noted in terms of operative time and hospital duration (95% CI: -18.95-8.80, MD = -5.08, P = .47; 95% CI: -.98- .58, MD = -.20, P = .61, respectively). Additionally, according to Clavien-Dindo Grade, the rates of major complications (>= Grade 3a) including open conversion (.8% vs 5.5%, 95%CI: -.11- .01, RD = -.05, P = .12), stone migration (8.1% vs 6.7%, 95% CI: -.08- .11, RD = .02, P = .76), vascular injury (5.4% vs 0, 95%CI: -.03- .14, RD = .05, P = .21) and ureteral stricture (1.3% vs 5.3%, 95% CI: -.11- .02, RD = -.04, P = .20), were comparable between the two groups. Conclusion: In the treatment of large and proximal ureteral calculi, LTU has a significantly higher single-procedure success rate and a higher rate of postoperative paralytic ileus than LRU. However, the complication was well-tolerated. The small sample size and limited, including studies, were the main limitations.